2005
DOI: 10.1001/archinte.165.6.667
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Advance Care Planning in the Veterans Affairs System

Abstract: This intervention demonstrates mixed results and highlights the ongoing challenges of helping health care providers and potential proxy decision makers represent patient preferences and values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
155
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(158 citation statements)
references
References 38 publications
2
155
0
1
Order By: Relevance
“…A second line of research examines the concordance between a patient and his or her doctors, [14][15][16][17][18][19][20][21][22][23][24] or chosen surrogates. 17,18,21,[25][26][27][28][29][30][31][32] In such studies, individuals are asked what they would want for themselves in particular circumstances.…”
Section: The Evidence Against Substituted Judgmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A second line of research examines the concordance between a patient and his or her doctors, [14][15][16][17][18][19][20][21][22][23][24] or chosen surrogates. 17,18,21,[25][26][27][28][29][30][31][32] In such studies, individuals are asked what they would want for themselves in particular circumstances.…”
Section: The Evidence Against Substituted Judgmentmentioning
confidence: 99%
“…They have generally been unsuccessful 32 or have improved predictions only modestly. 14,19 Finally, there has been extensive research examining whether patients really want their prior wishes to be the sole basis for decisions made on their behalf. This research reveals that the majority of patients prefer that family members or physicians have input into the decisions.…”
Section: The Evidence Against Substituted Judgmentmentioning
confidence: 99%
“…Overall, our results suggest that if clinicians were more active in talking to their patients about ACP, patients would be more likely to complete advance care directives. Successful interventions to increase advance directive completion in other patient populations have advocated direct clinician-patient communication, [25][26][27] education of health care providers, 28 and discussions with trained nursing or social work staff. 29 Similar strategies need to be applied to CF care, particularly by including discussions of advance care planning into routine medical visits.…”
Section: Sawicki Et Al 1138mentioning
confidence: 99%
“…47,54 Nevertheless, it is important for clinicians to assess patient's readiness for participation in ACP-discussions to adapt these discussions to the patient's needs. 58 …”
Section: Advance Care Planning (Acp)mentioning
confidence: 99%
“…35 A qualitative study identified the following major categories to describe barriers for ACP endorsed by loved ones: loved ones' attributes; access to physicians and information about ACP; and the interaction between physicians, patients, and loved ones. 58 Another cross-sectional study 59 shows that the most important barriers for talking about end-of-life care reported by loved ones are related to uncertainty about expected care and focus on staying alive instead of dying. In this study limited agreement was found between barriers reported by patients with advanced chronic organ failure and their loved ones.…”
Section: Barriers Endorsed By Loved Onesmentioning
confidence: 99%